2008
DOI: 10.1186/1471-2164-9-563
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-glucosyltransferase multigene family in Bombyx mori

Abstract: Background: Glucosidation plays a major role in the inactivation and excretion of a great variety of both endogenous and exogenous compounds. A class of UDP-glycosyltransferases (UGTs) is involved in this process. Insect UGTs play important roles in several processes, including detoxication of substrates such as plant allelochemicals, cuticle formation, pigmentation, and olfaction. Identification and characterization of Bombyx mori UGT genes could provide valuable basic information for this important family an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 38 publications
3
88
0
Order By: Relevance
“…It is, however, regarded as an important component of metabolic detoxification in insects, playing crucial roles in cuticular tanning (Hopkins and Kramer, 1992), pigmentation (Hopkins and Ahmad, 1991;Wiesen et al, 1994;Mizokami and Yoshitama, 2009), as well as detoxification. UGTs are encoded by a multigene family, which has been recently analyzed in several insects from which genomic information is available (Luque and O'Reilly, 2002;Huang et al, 2008). Further studies are necessary not only to determine which gene(s) is involved in the glucosylation of capsaicin but also to understand its regulatory mechanism, in relation to the host-plant adaptation of herbivores.…”
Section: Perspectivesmentioning
confidence: 99%
“…It is, however, regarded as an important component of metabolic detoxification in insects, playing crucial roles in cuticular tanning (Hopkins and Kramer, 1992), pigmentation (Hopkins and Ahmad, 1991;Wiesen et al, 1994;Mizokami and Yoshitama, 2009), as well as detoxification. UGTs are encoded by a multigene family, which has been recently analyzed in several insects from which genomic information is available (Luque and O'Reilly, 2002;Huang et al, 2008). Further studies are necessary not only to determine which gene(s) is involved in the glucosylation of capsaicin but also to understand its regulatory mechanism, in relation to the host-plant adaptation of herbivores.…”
Section: Perspectivesmentioning
confidence: 99%
“…We speculate that venom allergen 5 is important for cell growth and development. This gene may be a multifunctional protein, performing different functions at different stages, as do the insect UDP-glycosyltransferases that play important roles in detoxication of xenobiotics, cuticle formation, pigmentation, and olfaction (Huang et al 2008, Bozzolan et al 2014. The specific biological function of venom allergen 5 in Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The B. mori UGT sequences were collected from KAIKObase (Shimomura et al, 2009) and SilkDB (Duan et al, 2010) based on the gene names in a previous report (Huang et al, 2008), which however did not give the actual sequences. BLAST searches of unannotated genomic contigs in NCBI were also performed to obtain additional sequences.…”
Section: Blast Searches Of Insect Ugt Sequences From Public Databasesmentioning
confidence: 99%
“…The molecular identities of the insect UGTs are, however, relatively unknown compared to the other detoxification gene families in insects or to the vertebrate UGT gene families. Although the UGT gene families in D. melanogaster and in B. mori (Huang et al, 2008) have been reported, they have not been compared in the context of the diversity of other insects.…”
Section: Introductionmentioning
confidence: 97%